A Snapshot of Social Media: Camera Phone Practices. (29th April 2015) - Hjorth, Larissa; Hendry, Natalie
This paper provides a short summary on some of the key debates emerging around visual social media. In particular we discuss the role of camera phones in issues of intimacy and co-presence.